Mobile long range rfid reader for indoor positioning system (mlrips) - Santos, Ricardo Batista (2022)
The industry is evolving and is currently living in the 4th industry revolution. It is facing new concepts, such as IoT (Internet of Things), which can create networks of devices to monitor, send and collect data. It enables new ways of production, valuecreation, and real time optimization. This project makes use of passive RFID (Radio Frequency Identification) tags for indoor positioning systems (IPS), in the moulds industry allowing the localization of moulds or tools inside big warehouses. A solution was created using RFID tags and an array of readers attached to specific industrial zones, able to locate moulds or tools with a precision of half a meter. The tag position will be broadcasted using an industry standard communication protocol called OPC-UA (OPC Unified Architecture).